1996
DOI: 10.1152/ajplung.1996.270.5.l722
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine in isolated airways of rat, guinea pig, and human: species differences in role of airway mucosa

Abstract: Stored endogenous acetylcholine (ACh) and in vitro synthesis of [3H]ACh were measured in isolated, mucosa-intact and mucosa-denuded airways of rat, guinea pig, and humans. In addition, choline acetyltransferase (ChAT) activity and ACh content were measured in freshly isolated airway mucosa as well as in cultured epithelial cells of rat tracheas. Rat tracheas stored 25 nmol/g ACh, whereas guinea pig tracheas and human bronchi contained only 2-3 nmol/g ACh. When incubated with [3H]choline, the isolated airways o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 0 publications
2
60
0
Order By: Relevance
“…Previous studies from our laboratory and other laboratories have shown that acetylcholine and M3 receptors are expressed in a wide variety of normal endothelial and epithelial cell types (5)(6)(7)(8)(9)(10)(11)(12)(13). This suggests that cancers derived from these diverse cell types will similarly coexpress acetylcholine and M3 receptors.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous studies from our laboratory and other laboratories have shown that acetylcholine and M3 receptors are expressed in a wide variety of normal endothelial and epithelial cell types (5)(6)(7)(8)(9)(10)(11)(12)(13). This suggests that cancers derived from these diverse cell types will similarly coexpress acetylcholine and M3 receptors.…”
Section: Resultsmentioning
confidence: 73%
“…Recently, it has been established that acetylcholine is also widely synthesized by a variety of nonneuronal cell types, including keratinocytes (5), airway epithelial cells (6,7), glia (8), vascular endothelium (9, 10), placental trophoblasts (11), and ovarian follicular cells (12) among others (13). Expression of acetylcholine has been unambiguously shown in these cells and tissues as shown by the presence of choline acetyltransferase, the enzyme that synthesizes acetylcholine, and by demonstration of acetylcholine synthesis in these cells as measured by high-performance liquid chromatography (HPLC).…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery that lung cancers synthesize and secrete acetylcholine (ACh) that acts as an autoparacrine growth factor provides potential new targets to inhibit lung cancer growth. 3,4 It is well established that ACh is an important neurotransmitter in the central and peripheral nervous systems and acts via activation of ACh receptors (AChRs).Recently, it has been found that ACh is also widely synthesized by a variety of non-neuronal cell types including airway epithelial cells, 5,6 keratinocytes, 7 small and large intestine, gall bladder, 8 glial, 9 vascular endothelial, 10 immune cells and most common cancer cells such as NSCLC, SCLC, colon, glial and ovarian carcinomas. [11][12][13][14][15][16] Although the primary function has not yet been completely elucidated, the expression of ACh in many different cell types suggests that its roles will be fundamental and will present novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of nAChR in lung cancers derives from expression of nAChR in normal lung cells. Normal bronchial epithelial cells express nAChR as part of a cholinergic autocrine loop (13)(14)(15)(16) in which all proteins needed for cholinergic signaling are present, including the ACh-synthesizing enzyme choline acetyltransferase (ChAT), the vesicular ACh transporter (VAChT), the high-affinity choline transporter CHT1, the ACh hydrolyzing enzymes acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), nAChRs, and muscarinic ACh receptors (mAChR). We and others have also shown that the interaction of ACh with both nAChR and mAChR stimulates cell proliferation (11,(17)(18)(19)(20), and we have previously reported that SCLC similarly express this cholinergic autocrine loop and that muscarinic antagonists can inhibit SCLC cell proliferation.…”
Section: Introductionmentioning
confidence: 99%